2020
DOI: 10.1161/hypertensionaha.120.15036
|View full text |Cite
|
Sign up to set email alerts
|

Total Atherosclerosis Burden of Baroreceptor-Resident Arteries Independently Predicts Blood Pressure Dipping in Patients With Ischemic Stroke

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Also, patients in whom nocturnal non-dipping was evident and who had SVD on MRI, were more likely to have a severe stroke. Whereas our research does not have prolonged follow-up, other studies have shown that patients with nocturnal non-dipping patterns are at a higher risk of stroke and CAD ( 2 5 ). Finally, nocturnal non-dipping of the heart rate was also associated with significantly higher rates of silent strokes and SVD.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Also, patients in whom nocturnal non-dipping was evident and who had SVD on MRI, were more likely to have a severe stroke. Whereas our research does not have prolonged follow-up, other studies have shown that patients with nocturnal non-dipping patterns are at a higher risk of stroke and CAD ( 2 5 ). Finally, nocturnal non-dipping of the heart rate was also associated with significantly higher rates of silent strokes and SVD.…”
Section: Discussionmentioning
confidence: 64%
“…Common disorders associated with non-dipping include diabetes mellitus, obstructive sleep apnea, chronic renal failure, and secondary causes of hypertension (2)(3)(4). A recent report suggested that atherosclerosis-related dysfunction in the baroreceptor may be related to poor nocturnal dipping in patients with stroke (5). The "non-dipping" and "reverse dipping" patterns may result in a higher 24-h mean blood pressure level leading to greater pressure load and shear stress on vessels resulting in accelerated atherosclerosis (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of peripheral artery disease is also an important marker for systemic atherosclerosis involving the coronary, cerebral, and renal vascular territories ( 29 ). Severe atherosclerosis could make the arterial wall less deformable, thereby impairing patients' BP-regulating capacity ( 30 ). Once the baroreflex-mediated BP regulation suffered, BP variability would increase, causing cardiovascular events ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Warfarin-Aspirin Symptomatic Intracranial Disease Trial (WASIDT) [ 19 ] was used to assess the luminal stenosis in the intracranial arteries, and the North American Symptomatic Carotid Endarterectomy Trial (NASCET) [ 20 ] was used to measure the luminal stenosis in the extracranial arteries. According to the degree of atherosclerotic plaques and stenosis, semi-quantitative score was used to evaluate atherosclerotic conditions (0, no atherosclerotic plaque; 1 atherosclerotic plaque without evident lumen stenosis or stenosis < 50%; 2, stenosis 50-69%; 3, stenosis 70-99%; 4, occlusion) [ 21 ]. The intracranial atherosclerotic burden was calculated through summing the intracranial atherosclerotic scores of intracranial arterial segments, which were categorized into four grades of 0, 1, 2–3, and ≥ 4 scores [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the degree of atherosclerotic plaques and stenosis, semi-quantitative score was used to evaluate atherosclerotic conditions (0, no atherosclerotic plaque; 1 atherosclerotic plaque without evident lumen stenosis or stenosis < 50%; 2, stenosis 50-69%; 3, stenosis 70-99%; 4, occlusion) [ 21 ]. The intracranial atherosclerotic burden was calculated through summing the intracranial atherosclerotic scores of intracranial arterial segments, which were categorized into four grades of 0, 1, 2–3, and ≥ 4 scores [ 21 ]. Similarly, the extracranial atherosclerotic burden was counted through extracranial arterial segments, and categorized into four grades of 0, 1, 2–3, and ≥ 4 scores[ 21 ].…”
Section: Methodsmentioning
confidence: 99%